Multi-stable straw-like carbon nanotubes for mechanical programmability at microscale - Jia Liu; Yong Ma; Wanjie Ren; Fei Pan; Shu Guo; Yuli Chen; Bin Ding (International Journal of Smart and Nano Materials, 2024)
ABSTRACTInspired by macroscale 3D pixel mechanical metamaterials and microscale straw-like carbon nanotube, we propose a design of multi-stable straw-like carbon nanotubes (MSCNT) via optimizing the structure of a unit to obtain multiple stable states under displacement loading by molecular dynamics. The unit of MSCNT is mirror-symmetrically connected two truncated graphene cones with specific apex angles. By switching the LJ term in AIREBO potential, we verify that the bistability of unit is co-determined by snap-through instability and microscale adhesions. Moreover, we examine the validity of the multi-stability of the unit cells arranged in series and in parallels. Simulation results indicate that the MSCNT can achieve mechanical programmability in microscale, which triggers many potential applications in need of customizing nanoscale mechanical behaviors.